ECONOMIC FISH LANDED AT THE NUSANTARA FISHERY PORT (PPN) AWANG BAY - Yunarty, Yunarty; Renitasari, Diana Putri; Kurniaji, Ardana; Syahrir, Muhammad; Alauddin, Muhammad Hery Riyadi; Risman, Risman; Kusuma, Ni Putu Dian; Amalia, Ayu Rizki (Universitas Mataram, 2025)
Stocking density plays a very important role in the process of Whiteleg shrimp seeding. High stocking density in Whiteleg shrimp larvae will affect the growth and survival of the shrimp. This study aims to analyze the growth and survival of whiteleg shrimp larvae with different stocking densities. The research method used is experimental. This study consists of 1 stocking density treatment with a stocking density of 115 fish/L (treatment A) and 176 fish/L treatment (D) which is repeated 3 times. This study consists of 6 tanks with a volume of 13,000 liters. During the maintenance period, the larvae were given natural feed and artificial feed. The parameters tested were water quality (temperature, pH, DO and salinity), survival and growth parameters. Data analysis used ANOVA. The results of the study showed that the population in the form of a presentation of each larval stage of treatment A was significantly different from treatment D. Likewise, the results of the survival analysis of treatment A were significantly different from treatment B. This means that treatment A with a density of 115 fish/L had better survival compared to a density of 176 fish/L. However, the results of the analysis in treatment A were not significantly different from treatment D. This means that the stocking density does not affect the growth of post larvae. The recommendation for proper stocking density in larval maintenance to produce high survival is to use a stocking density of 115 fish/L